Reinventing mutual recognition arrangements lessons from international experiences and insights for the ASEAN Region. - Mendoza, Dovelyn Rannveig (Metro Manila, Philippines Asian Development Bank, 2017)
Governments and nonstate actors around the world have signed mutual recognition arrangements (MRAs), but while most of them share the goals of streamlining the recognition of foreign workers qualifications and boosting labor mobility, the MRAs vary considerably. Implementation challenges faced in the Americas, Asia and the Pacific, and Europe offer lessons for Asian policymakers seeking to operationalize the MRAs of the Association of Southeast Asian Nations (ASEAN).
Keywords: Asia; Social rights -- Asia; Electronic books